Contemporary relevance of jajmani relations in rural India. (December 2016) - Kumar, Mukul
Abstract: Jajmani is claimed to be a traditional Indian institution which institutionalized non-contractual, inter-familial and inter-generational reciprocity between landowning and other services providing castes 1 in rural India. Though it took care of some livelihood needs of service caste people it also involved their subservience and exploitation. Based on an ethnographic field study of a village in north India this research study looks closely at the changes happening in jajmani but also simultaneously tries to learn a few important principles about the form and substance of development for the future of mankind. Though jajmani is going to be history soon, it can be instructive in offering the idea of the importance of local/vernacular spaces in organizing social and economic lives of rural communities while imagining a less hegemonised community and world for human living.